Exploring the Relationship Between Leadership and Organizational Innovation - Mohammed, Fathiya Abubaker (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2016)
In recent years, innovation has become a very important ingredient for competitiveness, productivity and social gain in organizations. Innovation in achieving its goals and objectives depends on the leaders of the organization and their leadership styles. This study aimed to investigate the impact of Managerial Leadership Styles on organizational innovation. To achieve this aim, a questionnaire was developed and distributed to a sample of 103 subjects in the public banks in Sirte. Data was analyzed using SPSS. In order to test the hypotheses of the study, Pearson’s Correlation coefficients were used to determine the direction and strength of the relationship between independent variables and dependent variable. Two types of leadership styles, namely, autocratic and democratic were found to have direct relationship with the organizational innovation. The results show existence a different leadership styles in these banks, and the impact of democratic style was strongly positive to the organizational innovation. The autocratic style showed negative impact. This implies that democratic leadership is deemed suitable for organizational innovation in the government Banks under study. Implications of the findings were discussed further. Based on those results, the researcher recommend reinforcing democratic style, and some corrective procedures should be applied on autocratic.